Kompetensi Perawat Terhadap Keselamatan Pasien di Beberapa Rumah Sakit Pinggiran Sungai Aliran Barito - Rizany, Ichsan; Pertiwiwati, Endang; Setiawan, Herry; Jumbri, Muhammad; Rahmaniah, Laila; Rahman, Muhammad Rijali (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Patient safety incidents are still an unresolved problem in the hospital. Many factors that are cause this problemone of them is nurse competence. This study aimed to analyze the relationship between nurse competence andpatient safety in several hospitals on the Barito River banks. The research design used a cross-sectional design.The study was conducted on nurses in three hospitals (n = 155 people) with the inclusion criteria as an executivenurse, at least one year of work, and not leaving. Data were analyzed using the test Correlation Spearman. Theresults showed that the average nurse competence was 88.09, while the average patient safety was 54.21. Therewas a significant relationship between nurses' competence and the safety of hypertensive patients (p = 0.006; r =0.219). Nurses' right competence will provide services that are more effective, efficient, and safe for patients. Thisstudy concludes that there is a relationship between nurse competence and patient safety. The higher the nursecompetence, the higher the level of patient safety. Hospital managers are expected to place nurses according totheir competence, so that patient safety is guaranteed in the hospital.